In vivo evaluation of phage therapy against Klebsiella pneumoniae using the Galleria mellonella model and molecular characterization of a novel Drulisvirus phage species - Gustavo Quispe-Villegas; Gabriela I. Alcántara-Lozano; Diego Cuicapuza; Raúl Laureano; Brenda Ayzanoa; Pablo Tsukayama; Jesús Tamariz (Microbiology Spectrum)
ABSTRACT Multidrug-resistant (MDR) Klebsiella pneumoniae is challenging to treat with conventional antibiotic regimens, posing a threat to healthcare systems. Phage therapy presents a promising alternative treatment strategy; however, characterization of its efficacy and safety is required. Here, we describe the microbiological and molecular characterization of a novel bacteriophage with activity against MDR K. pneumoniae using a greater wax moth (Galleria mellonella) model system. A bacteriophage was isolated from hospital wastewater. Viral kinetics and phage stability were evaluated under varied pH and temperature conditions. The therapeutic efficacy of the phage was evaluated using MDR Klebsiella-infected G. mellonella larvae as an in vivo model. Phage titers and larva survival were compared in phage-treated and control groups. Genomic sequencing (Nanopore and Illumina) was used to classify the bacteriophage and identify any resistance genes or virulence factors present in its genome. Functional characterization demonstrated effective lytic activity, favorable burst size (161 PFU/cell), and an optimal MOI of 0.1. The phage demonstrated stability across a wide range of temperatures (8°C–40°C) and pH levels (4–8). Experiments using the G. mellonella model showed improved larval survival with phage treatment. The novel bacteriophage was identified as a new species within the genus Drulisvirus with no lysogeny-associated, antimicrobial resistance, or virulence genes detected. The new Drulisvirus phage identified is a promising candidate for treatment of infections caused by MDR K. pneumoniae.IMPORTANCEThe study describes a bacteriophage with potential for use in phage therapy against Klebsiella pneumoniae, one of the most clinically significant bacterial pathogens today. Microbiological and genomic characterization of the phage revealed advantageous properties for therapeutic applications, while also identifying a novel species within the Drulisvirus genus. These findings significantly contribute to our understanding of bacteriophage diversity and their utility in combating antibiotic-resistant infections. Moreover, the authors developed an in vivo preclinical model of MDR infection using Galleria mellonella larvae and successfully applied it to study the bacteriophage’s therapeutic efficacy. This model offers a robust and efficient platform for preclinical testing.